Pengaruh Model Pembelajaran Cooperative Script terhadap Hasil Belajar Ilmu Pengetahuan Sosial Siswa di Sekolah Menengah Pertama Negeri 32 Pekanbaru - Annur Rosida Siregar; Kusnadi Kusnadi; Sakilah Sakilah; Indah Wati; Alimuddin Alimuddin; Wardani Purnama Sari (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
The purpose of this study is to measure the effect of learning examples of the cooperative script learning model on students' social science, shows the impact on the learning achievement of SMPN 32 Pekanbaru students.This is because students' lack of success in learning Social Studies. did not achieve who have not yet reached the KKTP score of 75 applied by the school. A quantitative approach with a quasi-experimental method was used in this research. The population of this study was all the seventh-grade students, totaling 179 students. The sample size was 70 students: 35 of which were from class VII-2 (experimental group) and 35 of which were from class VII-4 (control group). The students were selected using a purposive sampling technique. The data was collected using observation, testing, and documentation techniques. Data analysis techniques included normality tests, homogeneity tests, linearity tests, hypothesis tests, effect size tests, and N-gain score tests. It can be proven through and data analysis, learning methods nalysis, the cooperative script learning model could affect student achievement. The hypothesis test results proved this, as fobserved was higher than the critical value, 3.202 > 1.691, and the significance level was 0.05 or 5%.which explains that the alternative hypothesis (Ha) can be accepted and the conventional hypothesis (Ho) is rejected.